The Role of Physical and Rehabilitation Medicine in Preventing Musculoskeletal Complications in Pediatric Hemophilia - Maria Agustina Sulistyo Wulandari; Ellyana Sungkar; Rachmat Zulkarnain Goesasi; Tertianto Prabowo (Indonesian Health Issue, 2026)
Background: Pediatric hemophilia is a hereditary bleeding disorder that leads to progressive musculoskeletal complications due to recurrent hemarthrosis, thereby increasing the risk of long-term disability and reduced quality of life. Objective: To examine the role of medical rehabilitation in preventing musculoskeletal complications in pediatric hemophilia. Methods: This study was conducted as a narrative literature review by searching articles through PubMed, Scopus, and Google Scholar using keywords related to pediatric hemophilia, musculoskeletal complications, hemarthrosis, hemophilic arthropathy, and preventive rehabilitation and management. The selected literature included original research articles, clinical guidelines, and systematic reviews relevant to children and adolescent populations. A descriptive-synthesis approach was used to integrate findings related to musculoskeletal complications and phase-based preventive rehabilitation strategies. Results: Complications include hemarthrosis, chronic hemophilic synovitis, hemophilic arthropathy, joint deformities, and muscle hematomas, which contribute to decreased muscle strength, limited joint range of motion, chronic pain, activity restriction, and reduced quality of life. Preventive rehabilitation integrated with coagulation factor prophylaxis includes functional assessment (HJHS and FISH), the acute-phase RICE protocol, hydrotherapy, isometric strengthening exercises, range of motion exercises, joint protection education, and the use of orthoses and mobility aids. Conclusion: Medical rehabilitation represents an essential non-pharmacological prophylactic pillar in preventing musculoskeletal complications in pediatric hemophilia.